THE INFLUENCE OF THE IMPLEMENTATION OF LEARNING MODEL, COGNITIVE STYLE AND INITIAL ABILITY TOWARD MATHEMATICS LEARNING RESULT STUDENT’S OF CLASS VIII AT SMPN 1 RANTEPAO - Sonny Yalti Duma (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2017)
The research was experiment which aimed to discover whether the learning model, cognitive style and initial ability influenced the student’s mathematics learning results in class VIII at SMPN 1 Rantepao. The population of the research was class VIII students at SMPN 1 Rantepao. The sample of the research was taken by using random sampling technique. The sample which was chosen was 4 classes, namely class VIII.6, VIII.8, VIII.9 and VIII.11. There were two variables in the research, namely independent and dependent variables. Independent variables were learning model, cognitive style and initial ability. While dependent variables were the student’s mathematics learning result. The learning model referred to cooperative learning model of Course Review Horay and Team Games Tournament type, while the cognitive style referred to Field Dependent and Field Independent. Similarly, the initial ability in this research referred to high and low initial ability. The instruments of the research were observation sheets, questionnaire, mathematics learning test result which covered pre-test and post-test, initial ability test, and cognitive style test (GEFT Test). The data of the research was analyzed by using linear regression with interaction factor. The result of the research showed that the student’s mathematics learning result were influenced by learning model, cognitive style and student’s initial ability